Formulation and evaluation of poly(lactic-co-glycolic acid) microspheres loaded with an altered collagen type II peptide for the treatment of rheumatoid arthritis. (18th August 2015) - He, Jintian; Li, Huiqi; Liu, Chao; Wang, Gaizhen; Ge, Lan; Ma, Shufen; Huang, Lijing; Yan, Shaofeng; Xu, Xiaohong
Abstract: The aim of this research was to evaluate the potential of water-in-oil-in-water (w/o/w) and solid-in-oil-in-water (s/o/w) emulsification techniques to prepare the altered collagen type II peptide AP268-270 (ACTP)-loaded poly(lactic -co- glycolic acid) (PLGA) microspheres to make ACTP more convenient as an rheumatoid arthritis treatment. Microspheres produced by the s/o/w method had higher drug encapsulation efficiency (69.7–79.8%) than those prepared by the w/o/w method (21.8–39.3%). In vitro drug release was influenced by the microencapsulation technique, molecular weight, and composition of the polymer. After intramuscular injection of the optimal formulation to Lewis rats, the concentration of ACTP peptide in serum reached its maximum level on day 3 and then remained nearly stable for approximately 4 weeks. In a collagen-induced arthritis rat model, a single intramuscular injection of ACTP-loaded PLGA microspheres had comparable efficacy to the intravenous injection of ACTP peptide solution once every other day.